"O Sweet Cautery" John of the Cross and the Healing of the Natural World - Frohlich, Mary (2016)
Contrary to what may appear in a superficial understanding of his spirituality, John of the Cross strongly affirms the goodness of creation and its capacity to mediate the presence of God. He specifically identifies the web of mutual interactions among creatures as a primary manifestation of divine love, and he affirms that the more a person participates in God, the more he or she participates fully and joyfully in this community of creatures. Activation of creation's full capacity to mediate divinity, however, depends on the full fruition of the human person in God. Experientially, this involves a lengthy process of a back-and-forth rhythm between the glimpse of God in creation and the complete renunciation of dependence on creaturely knowledge in favor of faith. John's writings invite us to participate in the healing of the natural world by pursuing this contemplative rhythm all the way to its fruitional climax.
Keywords: John of the Cross; contemplative transformation; Deep Incarnation; Ecospirituality; Healing; theology of creation